Sistem Pendukung Keputusan untuk Penerimaan Siswa Baru di MIN 2 Oku Dengan Metode Profile Matching - Husniawati, Husniawati; Majalista, Riya; Sari, Rani Puspita; Risalman, Nurmulia Risky (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The acceptance of new students is one of the important processes in the world of education that determines the quality of students in an institution. At MIN 2 OKU, the selection process is still done manually, which risks causing subjectivity and inefficiency in decision-making. To address this issue, a Decision Support System (DSS) was developed using the Profile Matching method. The purpose of this research is to design and build a DSS based on the Profile Matching method in order to improve the accuracy and efficiency of new student selection at MIN 2 OKU. This method is used to assess the suitability between the candidate students' profiles and the predetermined criteria, such as academic scores, potential academic tests, interviews, and memorization. This system helps the school provide objective and systematic assessments. The test results show that this decision support system is able to provide student admission recommendations more accurately, fairly, and transparently compared to the manual process. Therefore, this system is expected to improve the quality of the selection process at MIN 2 OKU.